The Religious Identity of Rohingya Refugees in Malaysia - Lukmanulhakim, Nur Nadia; Samuri, Mohd Al Adib bin (Studia Islamika, 2023)
This paper explores the role of religious identity in the experiences of Rohingya refugees in Malaysia. It explores how their religious identity shapes their social engagement, coping mechanisms, and integration approaches. In contrast to focusing solely on race, this study underscores the significance of religion, especially in a Muslim-majority country like Malaysia, where Rohingya seek refuge from religious persecution while upholding their faith. Through qualitative analysis, the paper examines post-migration challenges faced by Rohingya refugees in integrating with the host community and maintaining their religious identity. Despite sharing the Islamic faith with many Malaysians, Rohingya encounter difficulties in integration and often feel marginalized. They establish community-centric spaces to preserve their religious practices and cultural heritage. This research underscores the complex interaction between religious identity and social integration among Muslim refugees in Muslim-majority countries, offering crucial insights that will inform integration policies and interventions.